THE MOVEMENT TOWARDS SYMBOLISM WITH ARTHUR RIMBAUD (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the work of Arthur Rimbaud (1854-1891), one of the significant representatives of French literature of the late 19th century. Rimbaud's poetry, his very image and fate have long been a symbol of a brilliantly gifted personality in France. Even during his lifetime, his name was surrounded by legends, which were based on the dramatic twists and turns of the poet's biography, whose creative activity lasted only a few years and ended as soon as the author crossed his twenty-year mark. The artistic work of Rimbaud, who was a younger contemporary of V. Hugo, T. Gauthier, S. Leconte de Lisle, S. Baudelaire, G. Flaubert, E. Zola, P. Verlaine, developed in the course of dialogue and polemics with various trends of the second half of the century and reflected the formation of a new literary and artistic movement - symbolism, and also had an undeniable significant influence on a number of later trends of modernism.